Nilai Organoleptik dan pH Telur Itik Asin dengan Penambahan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) pada Level yang Berbeda - F Fitriani; Intan Dwi Novieta; I Irfan; Sity Nurbaya (JURNAL GALUNG TROPIKA, 2021)
The purpose of this study was to determine the organoleptic value and pH of salted duck eggs with the addition of dragon fruit peel extract (Hylocereus polyrhizuz) at different levels. This study used a completely randomized design (CRD) with 4 levels of treatment and 3 replications, namely without the addition of dragon fruit peel extract, dragon fruit peel extract 5%, 10%, and 15%. The results showed that the addition of red dragon fruit peel extract as a ripening agent significantly affected the pH and organoleptic value of salted duck eggs. The average pH value ranges from 6.10-8.3. The average organoleptic value on a scale of 1-5 for color ranged from 2.38 to 4.39, aroma 2.87-3.78, taste 3.86-4.73. At the same time, the average hedonic organoleptic value (preference level) ranged from 2.85 to 4.71. Overall, the best concentration for all observation parameters was the addition of 10% red dragon fruit peel extract.